The Influence of Product Quality, Brand Image and Brand Trust on Customer Loyalty Balifiber West Jakarta Area - Risyad Ramadhan; Resti Hardini; Kumba Digdowiseiso (Jurnal Syntax Admiration, 2023)
This study aims to determine the effect of product quality, brand image and brand trust on customer of Balifiber loyalty in the West Jakarta area. The population in this study used the Slovin sampling technique where the population taken was 96 people with a significance level of 95% and a standard deviation of 25%. This study uses primary data with data collection methods through questionnaires distributed to 96 respondents. The data analysis technique uses inferential analysis with multiple linear regression and uses the Statistical Product and Service Solution (SPSS) version 26.0 program. The results showed that Product Quality positively and significantly affected BaliFiber Customer Loyalty with a path coefficient value of 0.178 and a significant t of 0.019. Brand Image has a positive and significant effect on BaliFiber Customer Loyalty with a path coefficient value of 0.330 and a significant t of 0.000. Brand Trust positively and significantly affects BaliFiber Customer Loyalty with a path coefficient value of 0.443 and a significant t of 0.000.